Giant Enhancement of Ferroelectric Retention in BiFeO3 Mixed‐Phase Boundary. (11th August 2014) - Huang, Yen‐Chin; Liu, Yunya; Lin, Yi‐Tsu; Liu, Heng‐Jui; He, Qing; Li, Jiangyu; Chen, Yi‐Chun; Chu, Ying‐Hao
<x xml:space="preserve">Abstract</x> A large enhancement of nanodomain retention is shown in the mixed‐phase region of a strained BiFeO3 epitaxial film. The superior ferroelectric retention is attributed to a lower elastic‐energy density at the phase boundaries, which act as periodic pinning centers for the domain wall motion. This study delivers a new pathway of incorporating an elastic‐energy term to assist ferroelectric retention. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>